2020
DOI: 10.1111/jpy.13005
|View full text |Cite
|
Sign up to set email alerts
|

Ecoregional Characteristics Drive the Distribution Patterns of Neotropical Stream Diatoms

Abstract: We assessed the relative influence of ecoregional features in explaining diatom distribution in the Orinoco river basin. Ecoregions in the Colombian Orinoco can be seen as imprints of the evolutionary history of the basin, for their current biodiversity and physiographic features are the result of the geological and climatic shifts that have occurred since the Tertiary. Thus, they represent an ideal testing ground for studying the interplay between ecological and evolutionary processes shaping diversity patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Moreover, as research concerning our study area showed, high pH and a relatively high mineralization or oligotrophy were more common in this area [63,64]. Recent research reports diatoms behavior as consistent with SPH [65]; however, more evidence will be more conclusive. Samples with a high Dominance Index were inhabited by either generalists or specialists (group 1 and 2), which is consistent with observations reported by Soininen and Heino [66]; however, samples in group 3, which were more diverse, were dominated firstly by generalists and then specialists (contradictory to Soininen and Heino [66], but this was consistent with other analyses on lakes, as in e.g, [67,68]).…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, as research concerning our study area showed, high pH and a relatively high mineralization or oligotrophy were more common in this area [63,64]. Recent research reports diatoms behavior as consistent with SPH [65]; however, more evidence will be more conclusive. Samples with a high Dominance Index were inhabited by either generalists or specialists (group 1 and 2), which is consistent with observations reported by Soininen and Heino [66]; however, samples in group 3, which were more diverse, were dominated firstly by generalists and then specialists (contradictory to Soininen and Heino [66], but this was consistent with other analyses on lakes, as in e.g, [67,68]).…”
Section: Discussionmentioning
confidence: 54%
“…In total, we sampled 26 (for diatoms), and 32 (for insects) stream segments during the dry season of 2017 (January–February) (González‐Trujillo, et al, 2020; González‐Trujillo, et al, 2020). Briefly, sampling sites consisted of a segment including three consecutive riffles, representative of the stream's range of substrata types, flow velocities, channel widths and depths, and canopy cover.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, substratum mobility was measured as the percentage of high mobility substrata (gravel and sand) at every stream segment. Further information on environmental variables is provided by González‐Trujillo, et al (2020), González‐Trujillo, et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations